Survival to hospital discharge is equivalent to 30-day survival as a primary survival outcome for out-of-hospital cardiac arrest studies. (September 2021) - Majewski, David; Ball, Stephen; Bailey, Paul; Mckenzie, Nicole; Bray, Janet; Morgan, Alani; Finn, Judith
Abstract: Aim: The 2015 Utstein guidelines stated that 30-day survival could be used as an alternative to survival to hospital discharge (STHD) as the primary survival outcome in out-of-hospital cardiac arrest (OHCA) studies. We sought to ascertain the equivalence (concordance) of these two survival outcome measures. Methods: We conducted a population-based retrospective cohort study of OHCA patients who were attended by St John Western Australia (SJ-WA) paramedics in Perth, WA between 1999 and 2018. OHCA patients were included if they received either an attempted resuscitation by SJ-WA or bystander defibrillation; were a resident of WA; and were transported to a hospital emergency department (ED). STHD was determined through hospital record review and 30-day survival via the WA Death Registry and cemetery registration data. Results: The study cohort comprised a total of 7953 OHCA patients, predominantly male (70%), with a median (IQR) age of 63 (46–77 years), a presumed cardiac arrest aetiology (78.9%), and the majority occurred in a private residence (66.8%). Survival rates were identical for STHD and 30-day survival, with both being (13.78%, 95% CI: 13.02–14.54%) (p = 0.99). The overall concordance between the two survival rates was 99.6%. There were only 30 (0.4%) discordant cases in total: 15 cases with STHD-yes but 30-day survival-no; and 15 cases with STHD-no but 30-day survival-yes. Conclusion: We found that STHD and 30-day survival were equivalent survival metrics in our OHCA Registry. However, given potential differences in health systems, we suggest that 30-day survival is likely to enable more reliable comparisons across jurisdictions.